Scientific Perspective of Traditional Long-term Weather Forecasting System of Hindus in Sri Lanka - Piratheeparajah, N. (University of Ruhuna, 2020)
Weather forecasting is becoming complicated due to the rapid and unpredictable climate changes in many countries. Hence various groups of people use numerous weather forecasting systems worldwide. Many countries have promoted their local and indigenous knowledge in all sectors towards sustainable development in recent times. In this context, Sri Lankan Hindu Tamils follow the sentential almanac (Ragunathaiyar Suththa Vaakkiya Panchangam) for long- or short-term weather forecasting. This study attempts to identify the scientific perspective of the relationship between long-term weather prediction indicated in the almanac and actual weather observations and measurements. All weather-related data (annual total and average) for fifty years from 1970 were collected from the Department of Meteorology for 16 stations. The almanac was also gathered from the same years. The collected data were analyzed using the correlation analysis method, which indicated a strong positive correlation between the observed annual total rainfall and the almanac predicted malai marakkal. According to the almanac, when mars is the ruling planet of a year, that year has a scanty rainfall, and when the moon is the ruling planet, rainfall is very heavy; thus, the rainfall varies based on the minister planet. Also, the rainfall varies based on the megathipathi planet of each planet. The average temperature was very high during the Kandavanam period. The almanac and actual weather phenomena disclosed a strong relationship, and the almanac predicted weather forecasting is more accurate and reliable for the short-term and long-term weather forecasting usage. However, the reliability in weather prediction of the almanac primarily depends on the accurate and appropriate reading and writing of the literature. A correctly explained almanac could be a reliable source for long term weather forecasting and planning and development activities.
Keywords: Almanac; Weather; Correlation; Reliability; Forecasting